KEPEMIMPINAN TRANSFORMASIONAL PADA PROGRAM STUDI DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS MULAWARMAN (Administratio, 2019)
The Faculty of Social and Political Science is the oldest faculty at Mulawarman University which is the first university as well as the highest number of students in Kalimantan. Then to maintain its existence, the Faculty of Social and Political Science of Mulawarman University needs to emphasize its superiority in the context of increasing competitiveness against the Faculty of Social and Political Science in other tertiery institutions. Therefore, management of the study program needs to be led by keaders who have the appropriate leadership style for institutional development. Transformational leadership patterns refer to it with a number of characteristics: charismatic, can affect idealism, inspirational and able to encourage the intellectuality of organizational members. The object of this survey is the four Coordinators in the Study Program with the highest number of students in the Faculty of Social and Political Science of Mulawarman University, with respondents from the academic community which include lecturers, education staff and students. The survey results show that the current Study Program Coordinator of the Study of Government and the Public Administration has the ame weakness in the ability of individual consideration. However, they experienced a better increase in their ability to provide intellectual stimulation compared to the previous Study Program Coordinator as seen from the increase in academic and non-academic achievement. Other findings from this survey are that currently the Study Program Coordinator of the International Relations actually has a weak ability to have an ideal influence and the Coordinator of Communication Studies has actually decreased the ability to provide intellectual stimulation compared to the leadership of the previous Coordinator, so that the Communication Studies Study Program requires efforts to increase innovation more focused on the implementation of scientific activities and the production of academic works better.